Bremsstrahlung Spectra Characterization by Photo-Activation: Preliminary Results - Ntalla, E.; Vasilopoulou, T.; Georgolopoulou, P.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
A method for the determination of the bremsstrahlung spectra of medical linear accelerators by photo-activation measurements is discussed. A set of activation foils with different photonuclear reaction energy thresholds was irradiated at two linear accelerators of 15 and 23 MV. The activity induced was determined using a germanium detector based gamma spectrometry system. The spectrum was reconstructed using theoretical expressions for photons emitted by electron interactions in thick targets and cross- sections from the IAEA Photonuclear Data Library. The results of this study enable experimental validation of the functional forms of bremsstrahlung spectra commonly used in radiotherapy treatment planning in the clinical environment.